SPTBN2, a New Biomarker of Lung Adenocarcinoma - Wu, Chunli; Dong, Bo; Huang, Lan; Liu, Yafei; Ye, Guanchao; Li, Shihao; Qi, Yu (Frontiers in Oncology, 2021)
Objectives: The gene encoding β-III spectrin (SPTBN2) plays important roles in the occurrence and development of LUAD. However, this has not been reported. Herein, our study aimed to reveal the relationship between the expression of SPTBN2 and LUAD. Materials and methods: 20 pairs of LUAD cancer tissues and adjacent tissues were collected from patients. The MeRIP-seq determined that expression of SPTBN2 in LUAD samples was obviously higher than that in the adjacent normal tissues. The expression of SPTBN2 was obtained from the CCLE, GEO, and HPA databases. Used STRING website to obtain data on protein-protein interactions and the results were visualized by Cytoscape software. Furthermore, used MCODE plug-in of Cytoscape software to identify the functional modules of PPI. Performed gene enrichment analysis. Then the survival analysis was conducted by the Kaplan Meier plotter database. Used the TargetScan to predict the targeted miRNA. Finally, we use the tissues to verify the expression of SPTBN2 by RT-qPCR. A549 and H1299 was selected to transfection for the construction of blank group, si-SPTBN2 NC group, si-SPTBN2 group. Respectively, cellular proliferation, migration, and invasion were determined by experiment. Results: In the cell line level, the expression of SPTBN2 in non-small cell lung cancer (NSCLC) ranked thirteenth among cancer cell lines. In mRNA and protein levels, the expression of SPTBN2 was higher in LUAD tissues than that in normal lung tissues. KEGG Pathways disclosed that Proteins related to SPTBN2 were enriched in apoptosis pathway and phagosome pathway. KM survival analysis displayed that the SPTBN2 expression was significantly related to the prognosis of patients with lung adenocarcinoma. TargetScan database verified miR-16 negatively regulated the SPTBN2 mRNA expression. The results of CCK-8, wound healing assay, Transwell migration and invasion test showed knocking down SPTBN2 could significantly inhibited cell proliferation ability, migration and invasion ability. Conclusion: We uncovered a novel gene that was remarkably increased in LUAD tissues. The expression of SPTBN2 was higher in LUAD tissues than that in normal tissues. SPTBN2 is highly expressed in LUAD, positively correlated with poor prognosis, and can promote the proliferation, migration and invasion of LUAD cells.